The Ethics of Tax Evasion: An Approach on Variables Using Principal Component Analysis - Ribeiro, César; Pinho, Carlos Santos (Journal of Accounting and Finance, 2020)
The literature encompasses a relatively wide range of arguments regarding the perception of tax evasion as an ethical procedure. Each of these arguments stands for a valid variable for study, leading to an equally wide range of variables. Our study is aimed at addressing these variables using the Principal Component Analysis (PCA) and at identifying subsets of variables that may be strongly correlated with one another. As a result, regarding the eighteen initial eigenvalues, it was possible to create three new composite variables, all of them with satisfactory internal consistency results.